Comparison of two different stretching strategies to improve hip extension mobility in healthy and active adults: a crossover clinical trial - Ángel González-de-la-Flor; Charles Cotteret; Guillermo García-Pérez-de-Sevilla; Diego Domínguez-Balmaseda; Jose Ángel del-Blanco-Muñiz (BMC Musculoskeletal Disorders, 2024)
Abstract Objective To improve hip flexor flexibility, the commonly used hip extension stretch focuses on advancing the pelvis forward in a half-kneeling position, targeting only hip extension. This study aimed to compare the effectiveness of this traditional stretch with a new technique incorporating posterior pelvic tilt. Methods A randomized crossover clinical trial was conducted with in 26 healthy, physically active individuals (52 hips), aged 22.50 ± 4.10 years. Each participant performed both the hip extension stretch and the posterior pelvic tilt stretch (26 hips), with one technique applied to each limb: the posterior pelvic tilt stretch on one limb and the hip extension stretch on the other limb (26 hips). The reactive hip flexor test and active knee extension test were measured pre and post stretching techniques. A repeated measures ANOVA was performed to assess differences between groups. Results There was a significant group-by-time interaction with a medium effect size for the variable related to reactive hip flexor force (F = 4.775, p = 0.034, η2p = 0.087). The posterior pelvic tilt stretch had a statistically significant mean difference of 4.85 N·m (p = 0.003; 95%CI: 1.74; 7.96) compared with the hip extension stretch (mean difference = 0.06 N·m (p = 0.969; 95%CI-3.05; 3.17). No significant differences were found for active knee extension (p > 0.05). Conclusions The results showed that the posterior pelvic tilt stretching technique was effective in reducing the hip reactive flexor force when compared to conventional hip extension stretch.